ANALISIS USAHA AGROINDUSTRI DAN STRATEGI PENGEMBANGAN ROTI MERK GANDUM PADA PT ROTTE RAGAM RASA CABANG BUKIT BARISAN KOTA PEKANBARU PROVINSI RIAU - Rizki Herlangga; Fahrial (DINAMIKA PERTANIAN, 2023)
The bread business is a popular business because the need for bread never decreases because the level of public consumption of bread is always increasing. The community's need for bread shows that the opportunities in this business can still grow, one of which is by optimizing the agroindustry process. This study aims to analyze: (1) characteristics of entrepreneurs and business profiles of wheat bread; (2) analysis of wheat bread agroindustry business production technology, production factors, costs, income, profit, efficiency, and value added; and (3) wheat bread development strategy. The method used in this research is the survey method. The selection of respondents was done intentionally. Data were analysed using qualitative descriptive statistical analysis, quantitative analysis, the Hayami method, as well as SWOT and QSPM analysis. This research was conducted in Tenayan Raya District, Pekanbaru City, Riau Province, from February to July 2023. The results showed: (1) The characteristics of entrepreneurs were in the age group of 41 years and the age of employees with an average age of 22 years, the entrepreneur's education level was 17 years and the average employee's education level was 12 years, the entrepreneur's business experience was 6 years and the employee's experience was an average of 1 year, the entrepreneur's family dependents were 3 people; and the family dependents of employees had no dependents. The PT Rotte Ragam Rasa wheat brand bread agroindustry business profile was established on April 28, 2016. The scale of the business carried out was small. The number of workers in the processing process amounted to six people. (2) The analysis of the wheat brand bread agroindustry business consists of: Wheat brand bread production technology includes kneading, weighing, thinning, developing bread dough, baking/oven, cooling, packaging, and bread display. Use of production factors, which include use of tools, raw materials, and supporting materials. Production costs were obtained at Rp 215,412/ day, gross income obtained by wheat brand bread entrepreneurs was Rp 232,500 / day, and an RCR (revenue cost ratio) of 1.08. (3) In the development strategy of wheat brand bread, the priority strategy was to maintain and improve customer satisfaction through consistency in quality, variety, and innovation of wheat brand bread products.